Impact of Interstitial Pneumonia on the Survival and Risk Factors Analysis of Patients with Hematological Malignancy. (4th September 2013) - Chen, Wei-Liang; Tsao, Yu-Tzu; Chang, Tsun-Hou; Chao, Tsu-Yi; Kao, Woei-Yau; Chen, Yeu Chin; Ho, Ching-Liang
Abstract : Background . The emergence of interstitial pneumonia (IP) in patients with hematological malignancy (HM) is becoming a challenging scenario in current practice. However, detailed characterization and investigation of outcomes and risk factors on survival have not been addressed. Methods . We conducted a retrospective study of 42, 584 cancer patients covering the period between 1996 and 2008 using the institutional cancer registry system. Among 816 HM patients, 61 patients with IP were recognized. The clinical features, laboratory results, and histological types were studied to determine the impact of IP on survival and identify the profile of prognostic factors. Results . HM patients with IP showed a significant worse survival than those without IP in the 5-year overall survival (P = 0.027 ). The overall survival showed no significant difference between infectious pneumonia and noninfectious interstitial pneumonia (IIP versus nIIP) (P = 0.323 ). In a multivariate Cox regression model, leukocyte and platelet count were associated with increased risk of death. Conclusions . The occurrence of IP in HM patients is associated with increased mortality. Of interest, nIIP is a prognostic indicator in patients with lymphoma but not in patients with leukemia. However, aggressive management of IP in patients with HM is strongly advised, and further prospective survey is warranted.